Toward innovation-driven growth: Innovation systems and policies in EU member states of Central Eastern Europe - Zuzana Zavarská; Alexandra Bykova; Richard Grieveson; Francesca Guadagno (The Vienna Institute for International Economic Studies (wiiw), 2024)
This study builds on our previous analyses of a new growth model for the EU member states of Central and Eastern European (CEE), focusing on fostering innovation-driven development. We aim to explain the types of innovation systems and policies that enhance domestic innovation capabilities, drawing on global best practices. A critical evaluation of the current innovation landscape in EU-CEE countries is conducted, particularly in the context of the green and digital transitions. The study assesses the strengths and weaknesses of both national innovation initiatives and opportunities provided by EU industrial and technology policy frameworks. Based on these insights, we offer actionable policy recommendations to promote innovation-driven growth, enhance productivity, and boost economic convergence over the medium term, taking into account the unique political and historical contexts of the EU-CEE countries. Additionally, we prepare country-specific briefing notes tailored to the individual development needs and opportunities of each nation.
Keywords: O14; O31; O38; 330; Innovation policy; technological development; Central Eastern Europe; convergence